Local to global perspectives on forest and land fires in Southeast Asia - Daniel Murdiyarso (2018)
Forest and land fires are not new to the landscapes of Southeast Asia. Nevertheless, strikingly different perspectives persist about the significance of fires in the tropics to environmental changes and human well-being and consequently how they should be managed. Our synthesis of papers in this special issue suggests both trade-offs and complementarities in various policy responses with differing objectives. There are, however, at least three domains with high potential of meeting multiple objectives. First, is through identification, and improved management, of ecosystems vulnerable to fire under current and future climate. Agriculture, forestry and human settlements on peat land areas in Indonesia are candidates for such a focus. Second, is through building adaptive capacities to manage fire and related land and water resources. Investments in capacity at multiple levels are needed, but particularly at fairly local levels where stakeholders have strong incentives to manage fires appropriate to local contexts. Third, is through building awareness that fire management does not universally equate to fire suppression. Severe smoke haze episodes, for example, are also a result of timing of fires, and some fire-adapted ecosystems may depend on fire to persist. Finally, we emphasize that effective fire management is unlikely to be realized without greater engagement by research and policy with stakeholders in thoroughly exploring the full range of land and fire management options. Negotiation, compensation and trade-offs are probably inevitable. © 2007 Springer Science+Business Media, B.V.